A newspaper for immigrants. Spanisch-Italian interference in Expreso Latino - Gómez Sánchez, Elena (Linguistik Online, 2014)
This contribution studies Spanish-Italian interference appearing in Expreso Latino, a newspaper for Latino immigrants broadly distributed in Italy, which offers interesting examples of two closely related languages in contact. The data constitute a field for the study of more general aspects related to intercultural communication.